Atraksi Pertunjukan Tari Piriang Talam Badantiang di Sanggar Talang Sarumpun Kota Payakumbuh - Sandora Rahma Firlana; Hardi Hardi; Nurmalena Nurmalena (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This journal examines the Piriang Talam Bantiang dance attraction at Sanggar Talang Sarumpun as a form of performing art in the city of Payakumbuh. The method used is a descriptive-analytical qualitative research method, which involves presenting data obtained in the field and then analyzing it according to the research needs. This study employs the theory and opinions of Y. Sumadiyo Hadi regarding form to strengthen the writing. Additionally, it uses supporting theories from Dedi Supriadi on creativity. The results obtained from this research show that the Piriang Talam Bandantiang dance attraction is a form of performance that can attract the attention of the community to watch and enjoy, while simultaneously introducing Piriang Talam Bandantiang dance as a performing art in the region.